A Systematic Review and Quality Assessment of Therapeutic Group Process Questionnaires. Issue 3 (2nd July 2020) - Orfanos, Stavros; Burn, Erin; Priebe, Stefan; Spector, Aimee
ABSTRACT: The aims of this study were to systematically review the literature on questionnaire-based group process measures and assess the psychometric scale development properties of these measures. A systematic search of questionnaire-based measures of group process was conducted from four databases: PsycINFO, Medline, EMBASE and AMED. A quality assessment was undertaken using established criteria. Only studies that described the development of questionnaire-based scales were included. Seventeen studies which described thirteen measures were included in the analysis. The developed list highlights a range of questionnaires that can be used by clinicians and researchers seeking to measure either "specific therapeutic group mechanisms" or "overall group experiences." Further research should focus on developing the content validity of these scales by involving the target population during item selection and reduction.